Soluble Epoxide Hydrolase Inhibitors Regulate Ischemic Arrhythmia by Targeting MicroRNA-1 - Chen, Yanying; Liu, Qiong; Yang, Tian; Shen, Li; Xu, Danyan (Frontiers in Physiology, 2021)
Abstract Background: Soluble epoxide hydrolase inhibitors (sEHis) inhibit the degradation of epoxyeicosatrienoic acids (EETs) in cells, and EETs have antiarrhythmic effects. Our previous experiments confirmed that t-AUCB, a preparation of sEHis, inhibited ischemic arrhythmia by negatively regulating microRNA-1 (miR-1), but its specific mechanism remained unclear. Aim: To examine the role of serum response factor (SRF) and the PI3K/Akt/GSK3β pathway in t-AUCB-mediated regulation of miR-1 and the interaction between them. Methods/Results: We used SRF small interfering RNA (siSRF), SRF small hairpin RNA sequence adenovirus (shSRF), PI3K/Akt/GSK3β pathway inhibitors, t-AUCB and 14,15-EEZE (a preparation of EETs antagonists) to treat mouse cardiomyocytes overexpressing miR-1 and mice with myocardial infarction (MI). We found that silencing SRF attenuated the effects on miR-1 and its target genes KCNJ2 and GJA1 in the presence of t-AUCB, and inhibition of the PI3K/Akt/GSK3β pathway antagonized the effects of t-AUCB on miR-1, KCNJ2 and GJA1, which were associated with PI3Kα, Akt and Gsk3β but not PI3Kβ or PI3Kγ. Moreover, the PI3K/Akt/GSK3β pathway was involved in the regulation of SRF by t-AUCB, and silencing SRF inhibited the t-AUCB-induced increases in Akt and Gsk3β phosphorylation. Conclusions: Both the SRF and the PI3K/Akt/GSK3β pathway are involved in t-AUCB-mediated regulation of miR-1, and these factors interact with each other.